Pengaruh Likuiditas dan Struktur Modal Terhadap Nilai Perusahaan pada Perusahaan Sektor Food and Staples Retailing yang Terdaftar di Bursa Efek Indonesia Periode 2022-2025 - Yuni Sahara; Tio Devilishanti; Muzakir Muzakir (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of liquidity and capital structure on firm value in food and staples retailing sector companies listed on the Indonesia Stock Exchange during the 2022–2025 period. This research used a quantitative approach. The population in this study consisted of food and staples retailing sector companies listed on the Indonesia Stock Exchange during the 2022–2025 period. The sampling technique used was purposive sampling, resulting in 11 companies as research samples. Secondary data were used in this study in the form of financial statements of food and staples retailing sector companies listed on the Indonesia Stock Exchange during the 2022–2025 period. The analytical methods used were multiple linear regression analysis, t-test, and F-test. The independent variables used were liquidity and capital structure, while the dependent variable used was firm value. The results of this study indicate the multiple linear regression equation as follows: LN (Y) = 1.22 – 0.66 LN (X1) + 0.14 X2 + e. The results of the t-test show that: (1) liquidity has a significant effect on firm value, as evidenced by a significance value of 0.01 < 0.05 with a negative direction, (2) capital structure has a significant effect on firm value, as evidenced by a significance value of 0.00 < 0.05 with a positive direction. The results of the F-test indicate that liquidity and capital structure simultaneously have a significant effect on firm value in Food and Staples Retailing sector companies listed on the Indonesia Stock Exchange during the 2022–2025 period.